"Pickup" Car Type Frame Elements Study Performance, which are Made of Composite Materials - Nesterenko Sr., Mykola; Nadobko, Vitaliy; Virchenko, Viktor; Koroleviat, Vladyslav (International Journal of Engineering and Technology, 2018)
The cars frame structures advantages and disadvantages analysis is carried out. The car metal capacity reducing ways while simultaneously providing the rigid and strength characteristics of the frame are determined. It is proposed to use 3D-printing from the composite materials offered in this article when repairing the frame or when manufacturing new parts for automotive industry. The analytical studies of the stresses and displacements of the frame, made from the proposed composite materials, have been carried out.Â Â Â